Investigation of Job Creation in Economic Sectors of Ilam Using Input-Output Table - Bakhtiar Javaheri; Fateh Habibi; Elham Arefi (مجله توسعه و سرمایه, 2020)
Objective: Analyzing the employment rate and its structure in the country and its various regions requires precise cognition of capacities and potentials of sectors and their compliance in the regions in order to develop a balanced and moderate production and employment plan in each of sectors and regions. Therefore, This research for the purpose of increasing production and employment with respect to the inappropriate state of the labor market has been conducted. Methods: In this study, with deploying input-output framework of the Iranian Statistics Center in the year 2011 and regional accounts and statistical calendar of the year 2011 for Ilam province, first, Ilam input-output framework is estimated using semi-logarithmic corrected local quotients method (AFLQ), in the form of one regional tables 17, and then major sector of the providence from the aspect of employment is outlined. Results: Based on research findings “Other Services”, “agriculture”, “Post and Telecommunications” and “Education” sectors have the maximum employment potential and “Water”, “Services of residential building, non-residential and Real estate dealers ” and  “Mining”  sectors have the lowest employment potential. In the employment elasticity, the "Agriculture" sector the highest elasticity and the "Water" sector has the lowest possess the elasticity. Conclusion: By investing and paying more attention to key employment sectors in Ilam province, we can simultaneously create economic growth and employment in this province.